PENGARUH KARAKTERISTIK PRIBADI DAN DIMENSI SOSIAL TERHADAP KEMAMPUAN WIRAUSAHA PEREMPUAN - Iqbal Reza Fazlurrahman; Anna Fariyanti; Suharno Suharno (Forum Agribisnis, 2016)
This research aimed to (1) identify the personal characteristics and social dimensions of women entrepreneur, and (2) to analyze the influence of personal characteristics and social dimensions to women’s entrepeurial skills. The analysis used in this research are descriptive and quantitative by using Partial Least Square (PLS) modelling. Result found that both characteristics and social dimension positively and significantly influence entrepreneurial skills of women. Social dimensions is a strong predictor which positively and significantly influence the entrepreneurial skills.